ANALISIS PROBLEMATIKA PENDIDIKAN AGAMA ISLAM DAN SOLUSINYA DALAM MENGHADAPI ERA INDUSTRY 4.0 - Bima Fandi Asy'arie; Mulyadi Mulyadi (MUMTAZ : Jurnal Pendidikan Agama Islam, 2023)
The purpose of this study is to find out the problems faced by teachers in Islamic religious education, various problems faced by teachers in schools, and how solutions to these problems can be applied in the face of the industrial era 4.0 and globalization. The author uses a qualitative approach in literature research, with research data coming from various literature, such as journals, books, personal documents, and so on. The study's objectives are (1) to find out Islamic religious education in the era of globalization and the era of Industry 4.0, (2) to find out the problems of Islamic religious education and how to solve them. The results of this study focus on the problem of internal factors, which include (1) mastery of the material, (2) love for the teaching profession, (3) skills in teaching, and (4) evaluation of student learning. Then the problems from external factors are (1) classroom management, (2) application of learning methods and models, (3) interaction between teachers and students, and (4) use of learning media.